1994
DOI: 10.1210/jcem.78.1.8288709
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and insulin resistance.

Abstract: The associates of gout-obesity, hypertriglyceridemia, glucose intolerance, and hypertension, strikingly resemble those of insulin resistance. In the present study we determined whether hyperuricemia is associated with insulin resistance and, if so, whether this association can be explained by other components of the syndrome. For this purpose we quantitated insulin sensitivity (euglycemic clamp) in 37 nondiabetic subjects (aged 30-68 yr) exhibiting varying degrees of the metabolic syndrome (body mass index, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 39 publications
7
103
0
3
Order By: Relevance
“…This has been observed by others, 47 and recently Haffner and coworkers 12 confirmed this association in a prospective study: subjects with hyperinsulinemia had the highest risk of developing hypertriglyceridemia and low HDL cholesterol levels after 8 years of follow-up and also after adjustment for overweight and body fat distribution. Several mechanisms for this observation have been suggested, 68 such as an increased very-low-density lipoprotein (VLDL) production by increased availability of free fatty acids, a reduced VLDL clearance, or reduced adipose tissue lipoprotein lipase activity.…”
Section: Discussionsupporting
confidence: 70%
“…This has been observed by others, 47 and recently Haffner and coworkers 12 confirmed this association in a prospective study: subjects with hyperinsulinemia had the highest risk of developing hypertriglyceridemia and low HDL cholesterol levels after 8 years of follow-up and also after adjustment for overweight and body fat distribution. Several mechanisms for this observation have been suggested, 68 such as an increased very-low-density lipoprotein (VLDL) production by increased availability of free fatty acids, a reduced VLDL clearance, or reduced adipose tissue lipoprotein lipase activity.…”
Section: Discussionsupporting
confidence: 70%
“…SUA levels have been positively correlated with insulin resistance. 28,29 We observed that WC increased with increasing SUA levels ( Table 1). WC is a marker of visceral obesity, and a larger WC was correlated with a higher degree of insulin resistance.…”
Section: Discussionmentioning
confidence: 73%
“…In this regard, our data are consistent with reports relating insulin resistance not only with diabetes, dyslipidemia, hypertension, central obesity and microalbuminuria, but also hyperuricemia, hyperleptinemia, endothelial dysfunction, inflammatory status, thrombophilia, oxidative stress and liver steatosis. [42][43][44][45][46][47][48] In conclusion, the coexistence of multiple metabolic disorders in the single individual, also called Metabolic Syndrome, occurs very frequently in the general population. The syndrome is associated with several nonmetabolic abnormalities documenting thrombophilia, increased oxidative stress, inflammation, endothelial dysfunction, liver steatosis and leptin resistance.…”
Section: Discussionmentioning
confidence: 99%